Mortgage Developments in Iraqi Law: A Comparative Study - Sangar Ali Rasool; Latif Pirot Ali (QALAAI ZANIST JOURNAL, 2024)
As a result of the waves of contemporary economic and technical development, a group of movables has emerged, in which the transfer of possession is not conceivable, whether due to its nature or the importance it enjoys, as the law requires that legal actions be performed on it to fulfill a special formality, and therefore the rule of registration applies to the title deed instead of from the rule of possession in the movable. And when it becomes possible to mortgage these movables as the pledged money, then mortgaging them is accompanied by a set of legal problems related to the legal system of mortgage, which is that mortgaging these movables responds to the general theory of mortgage in the general rules of civil law, or is it subject to the commercial mortgage system outside the scope of civil law, Or any other compatible system? This research came to find solutions to these problems. The article was divided into two requirements, and the research was appended by mentioning its findings and recommendations.